Primary and secondary care approach to paediatric mental health conditions: a novel model of care - Farhana Sharif; Edmond Power; Sarah Taaffe; Patricia McLoughlin (BMJ Publishing Group, 2022)
The enforced isolation caused by the COVID-19 pandemic has led to an increase in mental health issues and severity of presentations to emergency departments in Ireland. Long waiting lists for both Psychology and Psychiatry are further impacting on children's mental well-being. We proposed the creation of a 'Happiness Toolkit' that can be given to children on presentation to their primary or secondary care provider with a mental health issue. The toolkit is comprised of six evidence-based techniques that are proven to boost self-esteem, develop resilience and promote positive mental health. A leaflet detailing the practices along with a physical 'box' that the children must make were created. This resource may therefore provide immediate support to those children that may endure long waiting periods, sometimes greater than a year and a half, for referral to tertiary services. Our toolkit allows children and their families to engage in positive mental health practices that may prevent regression during this waiting period and lead to improved mental health or cessation of symptoms.